Peningkatan Hasil Belajar IPA dan Bahasa Indonesia Tema 3 Melalui Problem Based Learning Berbantu Media Video di SD 4 Karangbener - Kurnia, Jenia; Utaminingsih, Sri; Masfuah, Siti (PGSD Universitas Muria Kudus, 2024)
This research aims to describe teacher skills, describe increasing science learning outcomes and improving Indonesian language learning outcomes using a problem based learning model assisted by video media on theme 3 Healthy Food.This research is classroom action research which was carried out in two cycles and each cycle consisted of three meetings. The subjects in this research were 5th grade students at SD 4 Karangbener, totaling 20 students. The variables in this research consist of the independent variable, namely the Problem Based Learning model and the dependent variable, namely teacher skills and learning outcomes. Data collection techniques use observation and test techniques. The data analysis technique uses descriptive data in the form of a percentage of teacher skills and mathematics learning outcomes.The research results showed that the application of problem based learning assisted by video media was able to improve teacher skills in cycle I, which obtained a percentage of 61% in the sufficient category and increased to 81% in the good category in cycle II. The application of the problem based learning model assisted by video media was able to increase science learning outcomes, increasing to 60% for minimum completeness with an average value of 71.8 in cycle I and increasing again to 75% for minimum completeness with an average value of 79.3 in cycle II and the application of the problem based learning model assisted by video media was able to increase Indonesian language learning outcomes, increasing to 65% for minimum completeness with an average score of 74 in cycle I and increasing again to 80% for minimum completeness with an average score of 82.5. Based on the research results, it is concluded that the application of the problem based learning model assisted by video media can improve teacher skills and learning outcomes for science and Indonesian language content.